Exception From Informed Consent: How IRB Reviewers Assess Community Consultation and Public Disclosure. Issue 1 (28th September 2020) - Chisolm-Straker, Makini; Nassisi, Denise; Daya, Mohamud R.; Cook, Jennifer N.B.; Wilets, Ilene F.; Clesca, Cindy; Richardson, Lynne D.
Abstract: Exception from Informed Consent (EFIC) regulations detail specific circumstances in which Institutional Review Boards (IRB) can approve studies where obtaining informed consent is not possible prior to subject enrollment. To better understand how IRB members evaluate community consultation (CC) and public disclosure (PD) processes and results, semi-structured interviews of EFIC-experienced IRB members were conducted and analyzed using thematic analysis. Interviews with 11 IRB members revealed similar approaches to reviewing EFIC studies. Most use summaries of CC activities to determine community members' attitudes; none reported using specific criteria nor recalled any CC reviews that resulted in modifications to or denials of EFIC studies. Most interviewees thought metrics based on Community VOICES's domains (feasibility, participant selection, quality of communication, community perceptions, investigator/IRB perceptions) would be helpful. IRB members had similar experiences and concerns about reviewing EFIC studies. Development of metrics to assess CC processes may be useful to IRBs reviewing EFIC studies.